2011
DOI: 10.4103/0975-3583.83036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of right ventricular septal versus apical pacing on plasma natriuretic peptide levels

Abstract: Background:To investigate the contribution of right ventricular (RV) pacing sites to the cardiac function, this study compares plasma B-type natriuretic peptide (BNP) levels during RV septal and apical pacing in patients implanted with a pacemaker.Materials and Methods and Results:Seventy-four consecutive patients with indication for permanent pacing were included. To provide for the possibility of appropriate subgroup analyses, patients were stratified according to their pacing mode into two groups: Those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…In total, 2,974 articles (with duplicates deleted) were identified by the literature search. Seventeen trials comparing mid‐ and long‐term cardiac functions and nine trials comparing electrical pacing parameters (six trials overlapped) qualified for our meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 2,974 articles (with duplicates deleted) were identified by the literature search. Seventeen trials comparing mid‐ and long‐term cardiac functions and nine trials comparing electrical pacing parameters (six trials overlapped) qualified for our meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…This elevation may be related to AV dyssynchrony or worsening mitral regurgitation secondary to right apical stimulation. In the analysis of this study, the ventricular pacing site was not discriminated, but it is known that its short-term effects are not completely elucidated 22 .…”
Section: Discussionmentioning
confidence: 99%
“…33,29,32,12,14 We considered 6 month follow up to be sufficient to detect relevant changes in natriuretic peptide however levels have been found after even shorter time periods when used in other clinical settings. 17,19,26 We could not fully achieve the blinding of the echocardiographer because the additional lead was visible in the right atrium and the difference between VVI pacing and AV synchrony was also apparent. Finally, the number of patients was relatively small in this study and the data resulting from these analyses should be considered as preliminary observations.…”
Section: Limitationsmentioning
confidence: 96%
“…They concluded that hemodynamic improvement could be substantially influenced by pacing mode, more than by pacing site. 26 Kojuri and colleagues found that level of pro-BNP is lower in double chamber pacing in comparison with single chamber pacing. Therefore, it seems that dual chamber pacing causes less LV dysfunction.…”
Section: Effect On Bnp Level and LV Dyssynchronymentioning
confidence: 98%